2007
DOI: 10.1089/dia.2007.0227
|View full text |Cite
|
Sign up to set email alerts
|

Lung Function Changes Related to Diabetes Mellitus

Abstract: Diabetic microangiopathy targets the lung as it does other organs. Even though respiratory dysfunction in most patients with diabetes is subclinical and rarely the presenting complaint, there are several reasons why pulmonary assessment is important: (1) Pulmonary function testing noninvasively quantifies physiological reserves in a large microvascular bed that is not clinically devastated by diabetes. (2) Subclinical loss of pulmonary reserves becomes overtly debilitating under conditions of stress, such as w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
61
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(65 citation statements)
references
References 78 publications
0
61
0
1
Order By: Relevance
“…This is mainly because the alveolar-capillary system is characterized by a great microvascular reserve, and pulmonary abnormalities are commonly subclinical in diabetic patient [4]. However, the loss of microvascular reserve in the lung may become clinically important, with increased risk of hypoxia, in case of acute or chronic pathological lung conditions, including pneumonia, chronic obstructive pulmonary disease, and asthma, or fluid overload secondary to heart failure [5].…”
Section: ■ Abstractmentioning
confidence: 99%
See 1 more Smart Citation
“…This is mainly because the alveolar-capillary system is characterized by a great microvascular reserve, and pulmonary abnormalities are commonly subclinical in diabetic patient [4]. However, the loss of microvascular reserve in the lung may become clinically important, with increased risk of hypoxia, in case of acute or chronic pathological lung conditions, including pneumonia, chronic obstructive pulmonary disease, and asthma, or fluid overload secondary to heart failure [5].…”
Section: ■ Abstractmentioning
confidence: 99%
“…Also, insulin resistance could alter lung volume and mechanical function via mediators such as leptin. Indeed, animal studies have provided evidence for leptin as a stimulant of ventilation, whereas researchers have also proposed an important role for leptin in lung maturation and development [5]. Studies further suggest a significant impact of leptin on specific respiratory diseases, including obstructive sleep apnoeahypopnoea syndrome, asthma, chronic obstructive pulmonary disease (COPD), and lung cancer [5].…”
Section: Mechanisms Of Lung Damagementioning
confidence: 99%
“…But this loss of microvascular reserve in the lung may become clinically important in case of acute or chronic pathological lung conditions like pneumonia, chronic obstructive pulmonary disease, asthma and heart failure and hence should not be disregarded. [37] …”
Section: Discussionmentioning
confidence: 99%
“…enzymatic glycosylation and thus eventually causes reduction in lung compliance and subsequent chronic airflow obstruction 5,6 .…”
Section: Discussionmentioning
confidence: 99%
“…Chronic hyperglycemia causes microvascular changes such as thickening of basal laminae in the smaller vessels of the lungs and ultimately causes reduction of vascular diffusing capacity 5 . It was also observed that hyperglycemia affects the lung by nonenzymatic glycosylation of chest wall and bronchial tree proteins which prevents lung expansion 6 .…”
Section: Introductionmentioning
confidence: 99%